PENGHINDARAN PAJAK: LEVERAGE, TRANSFER PRICING DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Rani, Sasiska; Zuliyana, Meti; Mayasari, Venny (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to analyze the effect of leverage and transfer pricing on tax avoidance, with firm size as a moderating variable. A quantitative approach was used, with a sample of 12 consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. The analysis methods applied were multiple linear regression and Moderated Regression Analysis (MRA). The results show that both leverage and transfer pricing have a significant positive effect on tax avoidance, while firm size has a significant negative effect. Furthermore, firm size is proven to moderate the relationship between leverage and transfer pricing with tax avoidance, weakening the influence of leverage while strengthening the influence of transfer pricing. These findings provide important implications for regulators to tighten supervision of leverage and transfer pricing practices and encourage large firms to enhance tax compliance.